ESL learners’ reading approaches of an academic expository text - Noorizah Mohd. Noor, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2010)
The primary purpose of the present study is to explore the reading approaches of ESL learners reading an academic expository text. Through phenomenography, this study aims to identify the variations or different ways in which six ESL learners read an academic expository text. The ability to read effectively is a prominent skill required in any academic or higher learning contexts. However, many first year students, specifically second language learners, who enter institutions of higher learning, are found to be unprepared for the reading demands placed upon them. The sample of this study involved six second-year Bachelor of Arts students, majoring in English Language Studies (ELS) at Universiti Kebangsaan Malaysia (UKM). Three instruments were used in the collection of data: reading text, in depth interviews and observations. Findings revealed variations that represented the deep and surface approaches of reading an academic expository text. Although changes were recorded with each reading, further research could enhance the representation of students‟ approaches to reading if analyzed at individual level.